Resiliência hídrica urbana: diretrizes e estratégias para sua incorporação em municípios com o uso de indicadores - Corrêa, Thais Helena Prado (Universidade Federal de São Carlos, 2021)
Developing new strategies and tools to analyze the dynamics of water resources can help change the paradigm in city planning, optimizing decision-making, to help cities to remain hydraulically secure through investments that transform opportunities into solutions, and facing the adversities. The term Resilience has been gaining notoriety and supporters, both in academia and in management, for the development of applicable interdisciplinary tools and models since 2010, when the UN used the term to define cities capable of efficiently recovering from effects of any kind of risks and disasters. However, Urban Water Resilience (UWR) is still a term that has been little studied, approached, systematized, and applied in research related to the management of water resources. Thus, this work was motivated by the need to obtain interpretive data for the theme of UWR, considering its potential and importance regarding the construction of Resilience in general. Given the above, this research aims to propose guidelines and strategies for the incorporation of the UWR in municipalities based on the use of indicators. To achieve the intended objective, the direct or indirect presence of UWR in Municipal Plans of medium-sized Brazilian cities that are signatories of the international program Making Cities Resilient: My City is Getting Ready program was sought. In the next step, the Urban Water Systems (Water Supply, Sanitary Sewage, and Urban Drainage) were analyzed from the Components and Variables related to the UWR. Then, indicators associated with systematized variables were proposed, which were used in the proposed method for the incorporation of the UWR by the municipalities. As a result, it was observed that none of the Municipal Plans explicitly mention the term Resilience, although some aspects have been considered directly or indirectly. The systematization carried out resulted in fifteen Components and thirty-nine Variables, for which fifty-three Indicators were proposed that allow the monitoring of the UWR. Although the common practice of Brazilian cities in the division of Urban Water Systems has been maintained, an important advance towards making the city more resilient would be through integrated management of these, considering the UWR. Adopting the paradigm of unification of Water Systems and taking into account UWR will enable cities to assess the present and build the future by becoming water-safe cities.
Urban water resilience: guidelines and strategies for its incorporation in municipalities with the use of indicators
Keywords: Resiliência hídrica urbana; Urban water resilience; Resiliência; Resilience; Gestão das águas urbanas; Urban water management; Sistemas hídricos urbanos; Urban water systems; Indicadores; Indicators; ENGENHARIAS::ENGENHARIA CIVIL